Government formation and termination - Schleiter, P (Oxford University Press, 2020)
Most of the time government formation and termination in parliamentary, semi-presidential, and presidential democracies entails a degree of bargaining between political parties and, where relevant, the president. This chapter reviews the literature that analyses these bargaining processes and their outcomes. It examines the motivations and resources of parties and presidents in negotiating cabinet representation, the attributes of cabinets, their durability, the different modes of cabinet termination, and the methodological challenges that studying cabinet formation and termination gives rise to. Since the 1990s, I argue, the confluence of the institutionalist turn in the literature on parliamentary governments and the rising interest in cabinet formation and termination among scholars who study semi-presidential and presidential democracies has lent increasing realism to models of government formation and termination. At the same time, the merger of these different research traditions highlights new challenges which are identified in the chapter’s conclusion.